Understanding the Fundamental Plane and the Tully Fisher Relation - Mould, Jeremy (Frontiers in Astronomy and Space Sciences, 2020)
The relation between early type galaxy size, surface brightness and velocity dispersion, “the fundamental plane,” has long been understood as resulting from equilibrium in their largely pressure supported stellar dynamics. The dissipation and feedback involved in reaching such an equilibrium through merger formation of these galaxies over cosmic time can be responsible for the orientation of the plane. We see a correlation between surface brightness enhancement and youth in the 6dF Galaxy Survey. Correlations of this “tilt” with stellar mass, age, concentration, shape, and metallicity now point the direction for further work on the resolved kinematics and structure of these nearby galaxies and on their initial mass function and dark matter component. On the face of it, the Tully Fisher relation is a simpler one dimensional scaling relation. However, as late type galaxies have bulges as well as disks, and, as the surface density of disks is only standard for the more massive galaxies, additional parameters are involved.